2020
DOI: 10.1155/2020/1569456
|View full text |Cite
|
Sign up to set email alerts
|

Is Long-Term Benzodiazepine Use a Risk Factor for Cognitive Decline? Results of a Systematic Review

Abstract: Background and Aims. Benzodiazepines have been widely used for long periods of time despite their adverse effects. The acute effects on cognition are well established. However, less is known about the long-term effects. This study critically reviewed existing evidence of the association between long-term exposure to benzodiazepines and risk of cognitive decline in adults. Methods. A systematic review with narrative synthesis was conducted. PubMed and PsycINFO databases were searched using combinations of keywo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 62 publications
1
25
0
2
Order By: Relevance
“…Consistent with previous systematic reviews, our meta-analysis suggests no impairment in global cognition among elderly BZD users ( 49 , 50 ). Interestingly, studies with young adults showed opposing results ( 51 , 52 ), suggesting BZD use significantly impairs participants’ global cognitive functioning.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous systematic reviews, our meta-analysis suggests no impairment in global cognition among elderly BZD users ( 49 , 50 ). Interestingly, studies with young adults showed opposing results ( 51 , 52 ), suggesting BZD use significantly impairs participants’ global cognitive functioning.…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, a multicenter study found that patients with RBD who converted to dementia rather than parkinsonism had a higher percentage use of clonazepam at baseline, at which the authors conjectured that more severe RBD might have led to a higher risk of dementia with a consequent requirement of more medication 35 . In the general population, there was a controversial association between benzodiazepine usage and future risk of dementia, 36‐39 and a recent large cohort study did not reveal any association between the use of benzodiazepines and subsequent dementia in patients with affective disorders 40 . In our study, there was a higher maximum dosage of clonazepam used in patients with RIS than those without.…”
Section: Discussionmentioning
confidence: 99%
“…20 Nonetheless, a multicenter study found that patients with RBD who converted to dementia rather than parkinsonism had a higher percentage use of clonazepam at baseline, at which the authors conjectured that more severe RBD might have led to a higher risk of dementia with a consequent requirement of more medication. 35 In the general population, there was a controversial association between benzodiazepine usage and future risk of dementia, [36][37][38][39] and a recent large cohort study did not…”
Section: Discussionmentioning
confidence: 99%
“…Alprazolam is a short-acting benzodiazepine and is associated with temporary memory impairment and slowing of psychomotor functions in older adults (Pietrzak et al, 2012). Although there is no strong evidence of the long-term effect of alprazolam and benzodiazepine medications more broadly on global cognitive functioning, the literature suggests that efforts should be made to taper doses and remove patients from benzodiazepines as soon as possible to avoid tolerance and physical dependence (Nader & Gowing, 2020; Navy et al, 2018). One of the reasons for higher overall use of anxiolytics, sedatives, and hypnotics in low-income individuals can be associated with the available evidence that individuals with low income are more likely to have diagnosed mood disorders or anxiety than high-income individuals (Sareen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%